THE EFFECT OF COMPUTER SELF-EFFICACY AND MODERNIZATION OF THE TAX ADMINISTRATION SYSTEM ON THE USE OF E-FILING IN REPORTING ANNUAL SPT OF INDIVIDUAL TAXPAYERS - Ahmad Junaidi; Putri Wahyuni; Yudi Partama Putra; Hesti Setiorini (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to determine the effect of Computer Self-Efficacy and Modernization of the Tax Administration System on the use of e-Filing in reporting Annual Tax Returns (SPT) by Individual Taxpayers at the Bengkulu Satu Pratama Tax Service Office. The research method used was a quantitative survey approach using primary data obtained through questionnaires distributed to 397 individual taxpayer respondents who used e-Filing. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS version 25 through descriptive statistical testing, data quality testing, classical assumption testing, and hypothesis testing. The results showed that Computer Self-Efficacy had a positive and significant effect on the use of e-Filing, and Modernization of the Tax Administration System had a positive and significant effect on the use of e-Filing. Simultaneously, Computer Self-Efficacy and Modernization of the Tax Administration System had a significant effect on the use of e-Filing in reporting Annual Tax Returns by Individual Taxpayers. The conclusion of this study indicates that improving taxpayers' ability and confidence in using technology and implementing increasingly modern tax administration systems can increase the use of e-Filing services in fulfilling tax obligations. Keywords: Computer Self-Efficacy; E-Filing; Modernization of the Tax Administration System; Tax; Individual Taxpayers